Ventricular Habronemiasis in Aviary Passerines - Jennifer N. Niemuth; Joni V. Allgood; James R. Flowers; Ryan S. De Voe; Brigid V. Troan (Case Reports in Veterinary Medicine)
A variety of Habronematidae parasites (order Spirurida) have been described as occasional parasites of avian species; however, reports on passerines are relatively uncommon. From 2007 to 2008, 11 passerine deaths at The North Carolina Zoological Park in Asheboro, NC, USA, were associated with ventricular habronemiasis, which was determined to be the cause of death or a major contributing factor in 10 of the 11 individuals. The number and species affected were 5 Red-billed Leiothrix (Leiothrix lutea), 2 Japanese White-eye (Zosterops japonicus), 2 Golden-headed Manakin (Pipra erythrocephala), 1 Blue-grey Tanager (Thraupis episcopus), and 1 Emerald Starling (Coccycolius iris). Affected animals displayed nonspecific clinical signs or were found dead. The ventricular nematodes were consistent in morphology with Procyrnea sp. Koilin fragmentation with secondary bacterial and fungal infections was the most frequently observed pathologic lesion. Secondary visceral amyloidosis, attributed to chronic inflammation associated with nematodiasis, was present in 4 individuals. An insect intermediate host is suspected but was not identified. Native passerine species within or around the aviary may be serving as sylvatic hosts.